Sekovska fara sv. Ane v Framu v prvi polovici 19. stoletja in mladi Pavel Turner - Ožinger, Anton (Studia Historica Slovenica, 2001)
The Josephine reforms brought about the establishment of the Fram parish, which had, by the elementary (trivial) school as of 1810, along with the parish, a decisive impact upon the upbringing, education and life-direction of the young Fram boy Pavel Turner, as it was a time, when the influence of the family, the school and the Church was more exclusive than in the XX century or today. It was favourable thereby that it was possible to uncover specially talented persons and also to enable the development of their exceptional abilities. Turner is certainly one among them
Keywords: biografije; cerkvena zgodovina; fara Sv. Ane; Fram; kulturna zgodovina; Turner, Pavel